2011
DOI: 10.1080/10632913.2011.566100
|View full text |Cite
|
Sign up to set email alerts
|

Cognition and Student Learning through the Arts

Abstract: An increasing number of recent research studies suggest connections between cognition, social and emotional development, and the arts. Some studies indicate that students in schools where the arts are an integral part of the academic program tend to do better in school than those students where that is not the case. This study examines home/school factors that contribute most to variance in student learning and achievement and the arts from over 8,000 students in grade 5.The findings suggest in-school arts pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…Thus, arts education 'for its own sake' is more seldom highlighted. In practice as well as in research, there is much attention paid on whether music provides cognitive and academic benefits for children, even if there are meta-analyses showing that many assumptions in this line of thinking are merely wishful thinking (Č rnčec, Wilson, & Prior, 2006;Melnick, Witmer, & Strickland, 2011). To claim that music is good for children's learning in mathematics, and language skills are often used to argue the importance of music in educational practices for children.…”
Section: Introductionmentioning
confidence: 98%
“…Thus, arts education 'for its own sake' is more seldom highlighted. In practice as well as in research, there is much attention paid on whether music provides cognitive and academic benefits for children, even if there are meta-analyses showing that many assumptions in this line of thinking are merely wishful thinking (Č rnčec, Wilson, & Prior, 2006;Melnick, Witmer, & Strickland, 2011). To claim that music is good for children's learning in mathematics, and language skills are often used to argue the importance of music in educational practices for children.…”
Section: Introductionmentioning
confidence: 98%
“…Hawai'i State Assessment (HSA) results for the 2012-2013 school year reveal Pomaika'i students outperformed those from neighboring elementary schools who would later attend the same middle school. Without controlling for countless variables such as family socio-economic status, level of parent education, or student involvement in extra-curricular activities, it is implausible to draw causal relationship between these academic achievements and involvement in arts integrated curriculum based on test scores alone (Melnick, Witmer, & Strickland, 2011). Winner, Goldstein, and Vincent-Lankrin (2013) suggest that, even though correlational data reveals how students who participate in a large number of arts courses have higher educational achievement (as measured by scores on verbal and mathematical tests), we cannot conclude that the arts are the cause of higher achievement.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…This is highlighted by art's ability to increase engagement in other subject areas, thus supporting those subjects and their goals for learning. Likewise, Melnick et al (2011) studied the academic advantage that the arts may provide to art students. It has been found that student success on academic tests tend to decrease when art programs are eliminated (Melnick at al., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Melnick et al (2011) studied the academic advantage that the arts may provide to art students. It has been found that student success on academic tests tend to decrease when art programs are eliminated (Melnick at al., 2011). Melnick et al (2011) analyzed data of about 8,000 fifth graders who participated in the Early Childhood Longitudinal Study, Kindergarten Class of 1998-99 (ECLS-K).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation